Delta8(14)-steroids in the bacterium Methylococcus capsulatus. - Bouvier, P (1976)
The 4,4-dimethyl and 4alpha-methyl sterols of the bacterium Methylococcus capsulatus were identified as 4,4-dimethyl- and 4alpha-methyl-5alpha-cholest-8(14)-en-3beta-ol and 4,4-dimethyl- and 4alpha-methyl-5alpha-cholesta-8(14),24-dien-3beta-ol. Sterol biosynthesis is blocked at the level of 4alpha-methyl delta8(14)-sterols.